The effect of common imaging and hot water maceration on DNA recovery from skeletal remains. (December 2015) - Frank, Emilie M.; Mundorff, Amy Z.; Davoren, Jon M.
Highlights: Hot water maceration for cleaning skeletal remains has minimal impact on the quality and quantity of recoverable DNA. Common imaging techniques, such as X-ray and CT scan, have minimal impact on the quantity and quality of recoverable DNA from skeletal elements. The baseline amount of DNA in one skeletal element can be higher or lower than another element. Abstract: Identifying human remains often begins with cleaning and imaging the material. Hot water maceration is used to remove adherent soft tissue from bone and radiographs are taken to better visualize osseous details. Heat and radiation are known to have harmful effects on DNA, but their ability to degrade DNA when used for cleaning and imaging has not been well studied. To better understand their individual and combined effects on the recoverability of DNA from bone, skeletal samples were subjected to (1) hot water maceration (62 °C for 45 min); (2) CT scanning (0.6 mm slices, 120 kV, 10.4 s); (3) X-ray (50 kVp, 150 mA, 0.03 s, 40 in); and (4) all 3 treatments combined. Forty-eight DNA samples were extracted, quantified and amplified with the AmpFLSTR ® Identifiler ® system. Nearly all of the processed samples had reduced RFU values relative to the unprocessed samples, indicating some amount of genetic loss. This loss did not always translate into loss of profile completeness, since only a few samples had a reduction in the number of loci detected after processing. DNA yields were not significantly reduced by any one of the processing methods, however the results indicate that the damaging effects are additive. It is possible that processing may reduce a bone's DNA reservoir and as more procedures are preformed, the pool of available genetic information might be diminished. Many intrinsic and extrinsic factors can affect the recoverability of DNA from bone. Collecting a DNA sample prior to processing avoids the negative effects from hot water maceration and radiological imaging.